Effects of stem cell therapy on preclinical stroke - Gita Serafika Shannon; Ratih Rinendyaputri; Sunarno Sunarno; Amarila Malik (Open Veterinary Journal)
Stroke, particularly ischemic stroke, is a leading cause of global mortality and disability. It is caused by blood flow obstruction and reduced oxygen delivery to brain tissue. Conventional treatments, such as tissue plasminogen activator (tPA) and mechanical thrombectomy (MT), have limited efficacy in repairing neural damage and carry risks of adverse effects. As a result, stem cell therapies, including mesenchymal stem cells (MSCs), have emerged as promising approaches for enhancing neural recovery and offering neuroprotection in ischemic stroke management. MSCs offer multifaceted benefits, such as reducing inflammation, protecting neurons, and promoting angiogenesis and neurogenesis. Recent evidence highlights the importance of MSC secretomes–extracellular vesicles (EVs) and exosomes rich in neuroprotective factors, such as microRNAs, proteins, and cytokines. These bioactive molecules demonstrated considerable efficacy in preclinical models by reducing neuroinflammation, preserving neurovascular integrity, and promoting cellular repair in ischemic environments. Preclinical in vitro and in vivo studies demonstrate the potential of the MSC secretomes to restore brain function after ischemic stroke. This is achieved by enhancing neuronal survival through mechanisms such as angiogenesis or vascular recovery, neuroprotection including modulation of immune or inflammatory responses, apoptosis, and autophagy–and promoting poststroke neurogenesis. This review explores the translational challenges and future potential of integrating conventional ischemic stroke therapies with stem cell-based or cell-free approaches. The present study synthesizes current insights into the role of MSC-derived secretomes from both in vitro and in vivo studies. [Open Vet J 2025; 15(2.000): 601-618]